Genotyping-Guided Discovery of Persiamycin A From Sponge-Associated Halophilic Streptomonospora sp. PA3 - Matroodi, Soheila; Siitonen, Vilja; Baral, Bikash; Yamada, Keith; Akhgari, Amir; Metsä-Ketelä, Mikko (Frontiers in Microbiology, 2020)
Microbial natural products have been a cornerstone of the pharmaceutical industry, but the supply of novel bioactive secondary metabolites has diminished due to extensive exploration of the most easily accessible sources, namely terrestrial Streptomyces species. The Persian Gulf is a unique habitat for marine sponges, which contain diverse communities of microorganisms including marine Actinobacteria. These exotic ecosystems may cradle rare actinomycetes with high potential to produce novel secondary metabolites. In this study, we harvested 12 different species of sponges from two locations in the Persian Gulf and isolated 45 symbiotic actinomycetes to assess their biodiversity and sponge-microbe relationships. The isolates were classified into Nocardiopsis (24 isolates), Streptomyces (17 isolates) and rare genera (4 isolates) by 16S rRNA sequencing. Antibiotic activity tests revealed that culture extracts from half of the isolates displayed growth inhibitory effects against seven pathogenic bacteria. Next, we identified five strains with the genetic potential to produce aromatic polyketides by genotyping ketosynthase genes responsible for synthesis of carbon scaffolds. The combined data led us to focus on Streptomonospora sp. PA3, since the genus has rarely been examined for its capacity to produce secondary metabolites. Analysis of culture extracts led to the discovery of a new bioactive aromatic polyketide denoted persiamycin A and 1-hydroxy-4-methoxy-2-naphthoic acid. The genome harbored seven gene clusters involved in secondary metabolism, including a tetracenomycin-type polyketide synthase pathway likely involved in persiamycin formation. The work demonstrates the use of multivariate data and underexplored ecological niches to guide the drug discovery process for antibiotics and anticancer agents.